Developmental Anatomy of Cerebellum of Long-Tailed Macaque (Macaca fascicularis) at the First Trimester of Gestation - Tri Wahyu Pangestiningsih; Irene Linda Megawati Saputra; Agnya Sinung Suminar (Jurnal Sain Veteriner, 2014)
Long tailed macaque was one of animal models in biomedical research because it has  many similarities with humans, both anatomical and physiological properties. There were many research about cerebellum associated with its role in the coordination of muscle activity. Understanding of normal development of cerebellum long tailed macaque may help to understand about the development in human cerebellum and its abnormalities. Embryonic and fetal brain samples were obtained through caesarean section and were  then made for histological preparation stained with cresyl violet. Staining results were observed using a microscope with a digital camera. Images obtained are processed by graphics software Adobe Photoshop CS 8.0. Cerebellum Macaca fascicularis Ed40 showed the isthmus and rhombic lip that were composed of ventricular layer, mantle layer, and marginal layer. Cerebellum Macaca fascicularis Fd55 showed future lobes and future  fissures, but the cortex and medulla are not bounded clear. The cortex consisted of the external granular layer, neuroblast basket, and neuroblast stellate, while the  medulla consisted of neuroblast deep cerebellar nuclei. From this research, we concluded that neurons were on stage of proliferation and migration in the embryo aged 40 days, then differentiated and migrated to form cortex  cerebellum and deep cerebellar nuclei at the age of 55 days, but the development of the cerebellum was not fully completed yet.